Development of an experimental model of neurocysticercosis-induced hydrocephalus. Pilot study - Filho, Pedro Tadao Hamamoto [UNESP] (2015)
PURPOSE: To develop an experimental model of neurocysticercosis-induced hydrocephalus METHODS: There were used 17 rats. Ten animals were inoculated with Taenia crassiceps cysts into the subarachnoid. Five animals were injected with 0.1ml of 25% kaolin (a standard solution for the development of experimental hydrocephalus) and two animals were injected with saline. Magnetic resonance imaging (MRI) was used to evaluate enlargement of the ventricles after one or three months of inoculation. Volumetric study was used to quantify the ventricle enlargement. RESULTS: Seven of the 10 animals in the cyst group developed hydrocephalus, two of them within one month and five within three months after inoculation. Three of the five animals in the kaolin group had hydrocephalus and none in the saline group. Ventricle volumes were significantly higher in the 3-months MRI cyst subgroup than in the 1-month cyst subgroup. Differences between cyst subgroups and kaolin group did not reach statistical significance. CONCLUSION: The developed model may reproduce the human condition of neurocysticercosis-related hydrocephalus, which exhibits a slowly progressive chronic course.